2013
DOI: 10.1055/s-0033-1350510
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Activated Three-Dimensional Multifrequency Magnetic Resonance Elastography for High-Resolution Mechanical Imaging of the Liver and Spleen

Abstract: Purpose: To introduce a novel in-vivo three-dimensional multifrequency magnetic resonance elastography (3D-MMRE) method for high-resolution mechanical characterization of the liver and spleen. Materials and Methods: Ten healthy volunteers were examined by abdominal single-shot 3D-MMRE using a novel patient-activated trigger system with respiratory control. 10 contiguous slices with 2.5?mm cubic voxel resolution, 3 wave components, 8 time steps, and 2 averages were acquired at 7 mechanical excitation frequenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 32 publications
2
19
0
Order By: Relevance
“…Moreover, definite conclusions on healthy abdominal organs relative stiffness remains to be determined. Across the literature and the different elastography techniques, the liver is commonly found to be relatively soft with a Young’s modulus between 5 and 10 kPa (Bensamoun et al 2011; Castera et al 2010; Guo et al 2014; Masuzaki et al 2007; Palmeri et al 2008; Yin et al 2007a), when the kidney is admitted to be stiffer (Arda et al 2011; Bensamoun et al 2011; Gallotti et al 2010; Gennisson et al 2012) as observed in this study. However the stiffness of the spleen and the pancreas are not as well established.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Moreover, definite conclusions on healthy abdominal organs relative stiffness remains to be determined. Across the literature and the different elastography techniques, the liver is commonly found to be relatively soft with a Young’s modulus between 5 and 10 kPa (Bensamoun et al 2011; Castera et al 2010; Guo et al 2014; Masuzaki et al 2007; Palmeri et al 2008; Yin et al 2007a), when the kidney is admitted to be stiffer (Arda et al 2011; Bensamoun et al 2011; Gallotti et al 2010; Gennisson et al 2012) as observed in this study. However the stiffness of the spleen and the pancreas are not as well established.…”
Section: Discussionsupporting
confidence: 57%
“…Using SWE in healthy volunteers, Arda et al (Arda et al 2011) showed that the spleen was softer (2.9 ± 1.8 kPa) than the pancreas (4.8 ± 3 kPa), when Leung et al (Leung et al 2013) found the spleen to be much stiffer (17.3 ± 2.6 kPa) than the liver (5.5 ± 0.7 kPa). Results from different ARFI studies also measured a higher stiffness in the spleen than in the liver (Cabassa et al 2015; Guo et al 2014), the pancreas and even the kidney (Gallotti et al 2010). More studies are needed to draw conclusions on the relative stiffness of abdominal organs both in human and small animal.…”
Section: Discussionmentioning
confidence: 95%
“…For MRE parameter recovery, we used the MDEV inversion algorithm proposed earlier [11,14] which provides two independent parameters, |G * | and φ, corresponding to the magnitude and the phase angle of the complex shear modulus G * . Compared with the previous work, we modified the reconstruction algorithm in a way that (i) six in-plane derivative components u j,k were used for inversion instead of three curl components and (ii) instead of solving an over-determined set of equations MA=B for M by MA T A=A T B (T denotes the vector transpose) we considered the unweighted average, i.e.…”
Section: Parameter Reconstructionmentioning
confidence: 99%
“…Using this technique, highly resolved maps of the magnitude (|G * |) and the phase angle (φ) of the complex shear modulus were obtained in the liver and spleen [11,14], the kidney [14] and the brain [15]. |G * | combines both elasticity and viscosity and therefore relates to the haptic material properties; φ quantifies the degree of fluidity, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Total scan time was approximately 6 min. Parameter reconstruction was based on multifrequency dual elasto-visco inversion as proposed in Guo et al (2014) and Hirsch et al (2013), yielding the magnitude (jG Ã j) and the phase angle (4) of the complex shear modulus of the liver. For comparison to THE, both parameters were converted to shear wave speed using…”
Section: Multifrequency Mrementioning
confidence: 99%